2017
DOI: 10.1016/j.jcma.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal smoking exposure during pregnancy on postnatal outcomes: A cross sectional study

Abstract: Our results demonstrated that maternal smoking exposure during pregnancy is associated with low birth weight and small chest circumference. Although the incidence of active smoking in Taiwanese pregnant women is low, most of them are exposed to passive smoking environment. Further studies are required to evaluate useful interventions to enhance a smoking-free environment during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 35 publications
7
24
1
1
Order By: Relevance
“…Physical comorbidities were positively associated with secondhand smoking, a nding that echoes previous research linking secondhand smoking during pregnancy to various negative health outcomes, such as preterm delivery, fetal growth restriction, spontaneous abortion, birth defects, and fetal death [1,2]. Secondhand smoking can also increase risk for atherosclerosis and cardiovascular diseases, lung cancers, oral and esophageal cancers, and bone marrow myeloid leukemia [9].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Physical comorbidities were positively associated with secondhand smoking, a nding that echoes previous research linking secondhand smoking during pregnancy to various negative health outcomes, such as preterm delivery, fetal growth restriction, spontaneous abortion, birth defects, and fetal death [1,2]. Secondhand smoking can also increase risk for atherosclerosis and cardiovascular diseases, lung cancers, oral and esophageal cancers, and bone marrow myeloid leukemia [9].…”
Section: Discussionsupporting
confidence: 75%
“…For instance, a cross-sectional study in Greece showed that 36% of women reported active smoking, but 94% of these women were exposed to passive smoking during pregnancy [7]. A similar study in Taiwan found that 7.2% of pregnant women smoked during pregnancy, and 40.6% of these women were exposed to secondhand smoking [1]. A study in southern China found that 2.63% of pregnant women had a history of smoking; of these, 52.15% were also exposed to secondhand smoke during their pregnancy [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention of smoking and exposure to smoking during pregnancy is an important global issue and requires further research. Maternal smoking was associated with LBW in our study, which concurs with the findings of many previous studies about the adverse effects of smoking exposure on pregnancy outcomes (56)(57)(58).…”
Section: Discussionsupporting
confidence: 93%
“…Pregnancy is an ideal opportunity to intervene with mothers and families to prevent and control tobacco use, and should be a priority for both tobacco control and maternal and child health care [22]. Our results are consistent with earlier studies on tobacco smoke exposure [19,23,24]. The fraction of active smokers (1.4%) was too low in our study to allow a specific analysis, but other studies demonstrate that active smoking is related to the same endpoints and only the impact seems to be more pronounced [25,26].…”
Section: Discussionsupporting
confidence: 90%